WRIPUB 2020
DOI: 10.46830/wrirpt.19.00081
|View full text |Cite
|
Sign up to set email alerts
|

Ending Conflicts Over Water: Solutions to Water and Security Challenges

Abstract: This report explores some of the thorniest water crises taking place across the developing world. In southern Iraq, severe water quality problems have triggered social unrest and violent protests. Recent droughts in India have prompted an exodus of farmers from the countryside in Maharashtra and dried up the reservoirs serving the city of Chennai. Across the African Sahel, there are violent conflicts between farmers and pastoralists over water and productive land resources. In Yemen, urban water systems have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 75 publications
0
32
0
1
Order By: Relevance
“…Political, social, war, and armed conflicts worsen the situation. But disputes over water also provoke various conflicts, sometimes even armed ones, with human casualties (GLEICK, ICELAND, TRIVEDI, 2020;LASSERRE, 2006). So far, these conflicts are overwhelmingly internal, but researchers do not rule out large-scale international clashes over water access and management (FARINOSI at al., 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Political, social, war, and armed conflicts worsen the situation. But disputes over water also provoke various conflicts, sometimes even armed ones, with human casualties (GLEICK, ICELAND, TRIVEDI, 2020;LASSERRE, 2006). So far, these conflicts are overwhelmingly internal, but researchers do not rule out large-scale international clashes over water access and management (FARINOSI at al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…So far, the parties have tried to solve problems by nonviolent means -diplomatically. When conflict arises that threatens human violence, famine, ecological disaster, or significant economic and economic losses, it tends to take place at the subnational level, that is, within states (GLEICK, ICELAND, TRIVEDI, 2020;LASSERRE, 2006). Agreeing with this position, we aim to elaborate on the historical examples of water conflicts, which occurred within one state, to determine the specifics of the causes of their occurrence and the possibilities of settlement or solution.…”
mentioning
confidence: 99%
“…According to the World Resource Institute (WRI), the Mediterranean area characterized by MENA Countries has the highest water stress globally. Israel, Lebanon, Jordan, and Libya suffer from severe water stress (Figure 3) [25]. In these Countries, the situation is linked to the pedoclimatic conditions of the regions and how water resources are managed.…”
Section: Water Resources In the Mediterranean Areamentioning
confidence: 99%
“…Climate change is expected to cause more extreme weather events that will amplify threats to water safety around the worldthus increasing the need to act. , Floods and storms brought on by climate change can interrupt utility services and damage key water infrastructure, forcing people to rely on water sources that pose safety risks . Furthermore, flooding often leads to outbreaks of waterborne illness due to cross-contamination between water distribution and sewage systems. , Less predictable global rainfall patterns, another result of climate change in many regions of the world, make planning for water emergencies more difficult still. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Although water safety is affected by climate change, , people may find it difficult to draw this link because of the abstract, distant, and uncertain nature of climate change. For example, only 22% of Spaniards working in the tourism industry perceived a direct connection between climate change and the risk of future water shortages . A study with Italian farmers found that a majority were concerned about climate change, but they disagreed about whether climate change would affect their water supplies and in which direction .…”
Section: Introductionmentioning
confidence: 99%